Exploring the Power of Hide-and-Seek: A Promising Approach to Foster Social Skills Development in Children at TK Al-Fadlilah Yogyakarta - Soniyatul Ummah, Evi; Sofarina, Dwi Amelia (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This scientific article investigates the potential of the game "Hide and Seek" in promoting children's social skills. While past research has extensively examined other facets of child development, the impact of "Hide and Seek" on children's social development remains underexplored and vaguely defined. Thus, this study aims to fill this knowledge gap. The research uses a quantitative experimental method, employing a "Pre-Experimental One Group Pretest Post-test Design" without a control group. A non-probability sampling technique with a saturated sample type is used. Findings reveal that "Hide and Seek" significantly enhances social skills among children at TK Al-Fadlilah, Yogyakarta, with teachers serving as essential facilitators in this process. Data analysis demonstrates a significant increase in social skills, represented by a Wilcoxon test score of 0.000, under the 0.05 threshold. However, the limitations of this study include a relatively small sample size and a single educational setting, restricting the generalization of the results. Future research involving larger, diverse samples and a focus on understanding the best ways "Hide and Seek" and similar activities can support early childhood social development is strongly recommended.